NARRATIVE FRAGMENTATION THEORY AND THE CONCEPTS OF INTERTEXTUAL AND TRANSTEXTUAL RELATIONS IN POSTMODERN LITERATURE - Ochilova Dilnoza (International Journal of Literature and Language Studies, 2026)
Postmodern literature is characterized by its rejection of traditional narrative conventions and its embrace of experimental forms of storytelling. Among its most significant features are narrative fragmentation, intertextuality, and transtextuality, which have transformed the ways literary texts are constructed and interpreted. This article examines the theoretical foundations of narrative fragmentation and explores the concepts of intertextual and transtextual relations as essential components of postmodern literary discourse. Drawing upon the theories of Julia Kristeva, Mikhail Bakhtin, Gérard Genette, and other prominent scholars, the study investigates how fragmented narratives and textual interconnectedness challenge notions of originality, coherence, and authorial authority. The article argues that these techniques not only reflect the complexity of contemporary reality but also encourage readers to participate actively in the creation of meaning. Through a theoretical analysis of postmodern narrative practices, the study highlights the significance of textual plurality in contemporary literary studies.